Uma Ocorrência Singular de Barita no Sudoeste Catarinense, Brasil - BASTOS NETO, ARTUR CÉZAR; JELINEK, ANDRÉA RITTER; SAVI, CLOVIS NORBERTO (Pesquisas em Geociências, 1997)
The paper describes the later mineral assemblage at the Santa Catarina fluorite mining district, recently recognized in the Cocal fluorite ore vein. In this assemblage, the barite crystals are perfect, centimetric and translucent. The habitprismatic, granted by pinacoides – and the forms association – prisms m 210, n 110, l 410 and d 101, bipyramids z 211, r 411 e y 111 and pinacoides a 100, b 010 and c 001 – are here firstly described. The mineral assemblage fils a pipe where deposition was controlled by mixing of ascending hydrothermal fluids with two types of cold descending fluids.